Engaging age-diverse workers with autonomy and feedback: The role of task variety - Marques, T.; Sousa, I. C.; Ramos, S. (Journal of Managerial Psychology, 2023)
Purpose. The aging of the population is changing the composition of the workforce in most developed countries. With increasingly older and age-diverse workforces, organizations need to redesign jobs to keep their workers healthy, happy, and productive across the lifespan. In the current research we integrate socioemotional selectivity theory and selection, optimization, and compensation theory with job design to investigate how certain job characteristics influence the work engagement of older and younger workers. Design/methodology/approach. In a two-wave survey with age-diverse employees from multiple organizations (N = 372), we explore how autonomy and feedback contribute to the engagement of older and younger workers, depending on levels of task variety. Findings. In the case of older workers the relationships between autonomy and engagement, and feedback and engagement are positive when task variety is low but nonsignificant when task variety is high. Conversely, in the case of younger workers the relationships between autonomy and engagement, and feedback and engagement are positive when task variety is high but non-significant when task variety is low. Originality. Our research is among the first to investigate the combined effects of different job characteristics on age-diverse employees’ engagement at work. Research limitations/implications. Our research contributes to the growing body of knowledge on aging and work, particularly the lifespan perspective on job design. Nonetheless, the correlational design warrants caution about drawing causal inferences. Practical implications. Our findings inform managers on how to combine autonomy, feedback, and task variety to design jobs that can engage the multi-age workforce.